ANALISIS PERAN STAKEHOLDERS DALAM UPAYA PENGEMBANGAN DESA WISATA DENGAN MENGGUNAKAN KERANGKA PENTAHELIX - Sintia Diah Kusuma; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The development of tourist villages has become one of the Government's commitments since 2017 to be able to develop their village potential. As with Cempaka Tourism Village, which became the first village in Tegal Regency to be designated as a Tourism Village based on the Decree of the Head of the Tegal Regency Youth and Sports Tourism Office number 556/18/0988/2017. Over time, a tourist attraction requires a development program. As for this study, the development of tourist villages is based on Central Java Provincial Regulation No. 2 of 2019 on concerning Empowerment of Tourism Villages in Central Java Province. The development of the tourist village contains four indicators, namely the development of tourism village infrastructure, tourism village marketing, institutional strengthening, and actors partnership. Through a qualitative descriptive approach, this study aims to analyze the role of each stakeholders in the development of the Cempaka Tourism Village which is incorporated in the pentahelix framework, namely the elements of Academics, Business, Community, Media, and Government. The results of the study show that each stakeholders is able to show his role in accordance with his responsibilities. However, some stakeholders are considered less than optimal in carrying out their roles. This later became one of the obstacles in achieving the Cempaka Tourism Village development program. In addition, the obstacles found in the field are the lack of understanding of existing regulations, limited budget, lack of quality of human resources, and lack of coordination and collaboration between stakeholders. This research produces recommendations so that the synergy and role of each stakeholders can run optimally by strengthening coordination, refocusing village funds in part to fulfill tourism needs, implementing training programs to improve the quality of human resources which are carried out intensely and continuously, and making official MoUs that bind between stakeholders.